LIGHTS - Auzani Zeda, Mohamed kassim (FSGK & UiTM, 2023)
Light is a lyrical abstract animation that connects lights, technology, and imagination. The work is based on my continuous fascination with light projections and the interplay between the physical and digital worlds. I seek to transcend the boundaries of real and virtual by projecting moving images on actual canvas, seeking to manipulate and question our perception of space. The integration of digital and physical elements intends to metaphorically explore how we perceive reality —the dance between what is visible and what remains hidden. The geometrical landscape emits inspiration from the most significant historical landscape for Muslims, Jabal Al Nour - which holds powerful story far beyond its physical existence. Drawing inspiration from 'the seen and the unseen', Light invites the viewers on a journey of discovery, where the boundaries of perception are redefined, and the hidden wonders of our existence illuminates.